2013
DOI: 10.1002/jctb.4065
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of surface energetics approach to Understand protein interaction to ceramic hydroxyapatite

Abstract: BACKGROUND: A surface thermodynamics approach can be utilized to understand protein interaction during adsorption chromatography. Ceramic hydroxyapatite has been widely used in the purification of biomolecules during downstream bio-processing. Protein interaction with this adsorbent is a complicated process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…This study investigates the applicability of interfacial chemistry techniques as a diagnostic tool to understand protein interactions at the nanoscale. The underlying assumption of proteins being nano‐colloidal particles is instrumental to apply extended Derjaguin, Landau, Verwey and Overbeek (DLVO) theory , and subsequently investigate the interaction of these proteins to chromatographic beads via surface thermodynamic calculations. According to extended DLVO theory, the interaction energy between a colloidal particle (protein) and a solid support (chromatographic bead) is the cumulative sum of Lifshitz–van der Waals (LW), acid–base (AB), and electrostatic (EL) energies as shown in Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigates the applicability of interfacial chemistry techniques as a diagnostic tool to understand protein interactions at the nanoscale. The underlying assumption of proteins being nano‐colloidal particles is instrumental to apply extended Derjaguin, Landau, Verwey and Overbeek (DLVO) theory , and subsequently investigate the interaction of these proteins to chromatographic beads via surface thermodynamic calculations. According to extended DLVO theory, the interaction energy between a colloidal particle (protein) and a solid support (chromatographic bead) is the cumulative sum of Lifshitz–van der Waals (LW), acid–base (AB), and electrostatic (EL) energies as shown in Eq.…”
Section: Introductionmentioning
confidence: 99%
“…It has also helped study the interaction of various types of biomass with expanded bed chromatographic beads in several modes of operation . Protein interactions to certain chromatographic supports have also been studied, where early or late eluting proteins could only be marginally discriminated . The aim of this work was to investigate the fundamental effect of ligand chemistry on protein retention and test the validity of extended DLVO (xDLVO) calculations toward predicting protein–adsorbent interactions.…”
Section: Introductionmentioning
confidence: 99%
“…e and e o are the relative dielectric permittivity of medium and the permittivity in a vacuum, respectively. 28,29 Since the XDLVO theory is based on the LW, AB, and EL interactions, in a short-range region (separation distance < 5 nm), we hypothesized that all three types of interactions, especially AB interactions, are critical in governing the protein adsorption process. w 01 and w 02 are the surface potentials of the protein molecule and the flat substrate, respectively, which are correlated to their zeta potentials (f 1 and f 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the zeta potential of lactoferrin at pH 7.4 is 9.5mV. Muhammad Aasim et al reported that the calculated z-potential of hydroxyapatite was slightly negative at all kinds of pH system [36] . Therefore, the positive electrostatic carried Arg, are usually contributed to the adsorption to hydroxyapatite surface [37] .…”
Section: Zeta Potential Of Lactoferrinmentioning
confidence: 94%